Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika Kelas V UPT SPF SDN KIP Bara-Barayya 1 - Sayidiman; Putri Atjo, Syamsuryani Eka; febriani, sri (ETEDU : Elementary of Teacher Education, 2024)
The problem in this study is the low mathematics learning outcomes of students. The objectives of this study are: (1) To overcome the description of the use of the Group Investigation Type Cooperative Learning Model on Mathematics learning outcomes, (2) To find out the description of mathematics learning outcomes, (3) To find out the effect of the use of the Group Investigation Type Cooperative Learning Model on students' Mathematics learning outcomes. This study uses the Quasi Experimental approach of the Nonequivalent Control Group Design Type. The research variable is the Cooperative Learning Type Group Investigation learning model. The population of the entire study was 45 students in class V-B as the experimental class and class V-A as the control class at UPT SPF SDN KIP Bara-Barayya 1. The data analysis technique used was inferential analysis, it was obtained that the data produced in this study were normally distributed and homogeneous. Hypothesis testing using Independent Sample T-test data showed that there was an effect on students' mathematics learning outcomes. It can be concluded that the research shows that (1) The description of the implementation of the learning process using the Group Investigation Type Cooperative Learning Model shows that each stage of the learning implementation can take place effectively and is categorized as very high, (2) The description of the mathematics learning outcomes of students after implementing the Group Investigation Type Cooperative Learning Model reaches a very good category, (3) The Cooperative Learning Type Cooperative Learning Model has a significant influence on the mathematics learning outcomes.